2015
DOI: 10.1152/ajpgi.00067.2015
|View full text |Cite
|
Sign up to set email alerts
|

Circular and longitudinal muscles shortening indicates sliding patterns during peristalsis and transient lower esophageal sphincter relaxation

Abstract: Esophageal axial shortening is caused by longitudinal muscle (LM) contraction, but circular muscle (CM) may also contribute to axial shortening because of its spiral morphology. The goal of our study was to show patterns of contraction of CM and LM layers during peristalsis and transient lower esophageal sphincter (LES) relaxation (TLESR). In rats, esophageal and LES morphology was assessed by histology and immunohistochemistry, and function with the use of piezo-electric crystals and manometry. Electrical sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…2B). We found that during peristalsis there is greater axial shortening of the circular muscle layer than the longitudinal muscle in the distal esophagus, and the reverse happens during TLESR (67). Circular muscle contraction causes axial shortening of the esophagus because of its spiral orientation along the axis of the esophagus.…”
Section: Patterns Of Contraction Of the Two Muscle Layers During Peristalsis And Transient Les Relaxationmentioning
confidence: 71%
“…2B). We found that during peristalsis there is greater axial shortening of the circular muscle layer than the longitudinal muscle in the distal esophagus, and the reverse happens during TLESR (67). Circular muscle contraction causes axial shortening of the esophagus because of its spiral orientation along the axis of the esophagus.…”
Section: Patterns Of Contraction Of the Two Muscle Layers During Peristalsis And Transient Les Relaxationmentioning
confidence: 71%
“…It is critical to note that the localization of drug release could vary significantly when performed in vivo. The introduction of peristaltic and segmentation movements, [ 70 ] as well as varying fluid and mucus content will result in lower predictability in delivery localization. Still, location specific delivery is significantly enhanced using this mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we found that the SM decreased post-POEM GERD incidence compared with LM regarding abnormal acid reflux. It has been proven that the circular muscle may contribute to esophageal shortening due to the spiral-shaped structure and the role that it plays in axial movements [ 13 , 23 , 32 ]. Hence, circular muscle keeps reflux of stomach contents from entering the esophagus and thus pushes refluxate downward and back into the stomach again theoretically.…”
Section: Discussionmentioning
confidence: 99%